The Work of Gabriele Paleotti (1522–1597), Archbishop of Bologna, in the Context of the City’s Scientific and Artistic Life in the Early Modern Period - Prikladova, Mariia A. (Actual Problems of Theory and History of Art, 2022)
Following the decrees of the Council of Trent (1545–1563), issues related to sacred images, their role and iconography of Holy images became the subject of a number of European treatises of the 16th–17th centuries. The paper is dedicated to Gabriele Paleotti’s work, in particular, to his “Discorso intorno alle immagini sacre e profane” (1582) in the context of Bologna’s scientific and artistic life in which the cardinal was greatly involved. The author draws parallels between G. Paleotti’s work and U. Aldrovandi’s one. The archbishop’s attempt to strictly regulate art and create a universal language understood by everyone, did not find wide support both among the masters and priests. G. Paleotti’s work, possibly influenced by C. Borromeo, was a product of his time. Meanwhile the desire for unification did not correspond to the needs of the period, with its craving for experiments, a variety of artistic directions, tasks and aesthetic preferences, an increasingly secular orientation of art and aspiration for freedom of expression. Under these conditions, the work of G. Paleotti rather summarizes the wishes of the 16th century than gives a new impact to the development of art in the 17th century.
Keywords: Italy; Counter-Reformation; 16th century; 17th century; Gabriele Paleotti